Effect of Earning Per Share, Net Profit Margin on Stock Returns in Property and Real Estate Companies - Dessyana, Dessyana; Aliah, Nur; Hayati, Keumala (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
This study aims to determine the effect of Earning Per Share, Net Profit Margin on Stock Returns in property and real estate companies. This study used a descriptive quantitative approach, where this research was conducted by managing data in the form of numbers processed with the SPSS application. The sample from this study was 31 samples with an observation sample of 155 samples (2015 -2019). The results of this study are that Earning Per Share has no effect on stock returns, but Net Profit Margin has a significant effect on stock returns. The Net Profit Margin value will show sales success and achievement of the company's profit target, this will motivate investors to invest because they expect a good return